ROLE OF EDUCATION POLICY - Sugito Muzaqi; Muchamad Arif (Universitas Narotama, 2022)
The background of this research is to find out the differences and similarities in the curriculum between Indonesia, Malaysia and the Philippines regarding Islamic religious education curriculum policies implemented in Indonesia, Malaysia and the Philippines. the role of policy will determine the direction of how to deal with the era of the industrial revolution. Islamic religious education will be synergized with government policies, especially in the management of educational institutions, especially the implementation of the curriculum that will be applied to each country. This curriculum will answer various problems that develop in society. The method used is a literature study using a qualitative approach, the data will be processed from the government policies of each country in order to find out how important it is to the results of the determination. The implementation of the curriculum in Islamic education in Indonesia, Malaysia and the Philippines is almost the same, namely in the form of an education unit level curriculum